Primitive ATP-activated P2X receptors: discovery, function and pharmacology - Fountain, Samuel J. (Frontiers in Cellular Neuroscience, 2013)
Adenosine 5-triphosphate (ATP) is omnipresent in biology. It is therefore no surprise that organisms have evolved multifaceted roles for ATP, exploiting its abundance and restriction of passive diffusion across biological membranes. A striking role is the emergence of ATP as a bona fide transmitter molecule, whereby the movement of ATP across membranes serves as a chemical message through a direct ligand-receptor interaction. P2X receptors are ligand-gated ion channels that mediate fast responses to the transmitter ATP in mammalian cells including central and sensory neurons, vascular smooth muscle, endothelium, and leukocytes. Molecular cloning of P2X receptor and our understanding of structure-function relationships has provided sequence information with which to query an exponentially expanding wealth of genome sequence information including protist, early animal and human pathogen genomes. P2X receptors have now been cloned and characterised from a number of simple organisms. Such work has led to surprising new cellular roles for the P2X receptor family and an unusual phylogeny, with organisms such as Drosophila and C. elegans notably lacking P2X receptors despite retaining ionotropic receptors for other common transmitters that are present in mammals. This review will summarise current work on the evolutionary biology of P2X receptors and ATP as a signalling molecule, discuss what can be drawn from such studies when considering the action of ATP in higher animals and plants, and outline how simple organisms may be exploited experimentally to inform P2X receptor function in a wider context.